Methodology And Application of Innovative Technologies to Ensure Sustainable Development: Formation of Eco-Awareness Through the Prism of Ecotourism - Borutska, Yuliia; Dydiv, Iryna; Krupa, Oksana; Hryhorieva, Liudmyla; Sylkin, Oleksandr (Journal of Ecohumanism, 2024)
The formation of eco-awareness through the prism of ecotourism is of paramount importance in today's world as it addresses the pressing need for sustainable interaction with our environment. The purpose of the article is to define the methodology and forms of application of innovative technologies to ensure sustainable development: formation of eco-awareness through the prism of ecotourism. The task is to apply innovative technologies to ensure sustainable development: formation of eco-awareness through the prism of ecotourism. Ecotourism serves as a powerful educational tool, offering individuals first-hand experiences of natural environments while promoting conservation and sustainability. The object of the study is the formation of eco-awareness through the prism of ecotourism. The methodology of the study involves the use of the IDEF0 method. As a result of the study, a model for ensuring sustainable development is presented: formation of eco-awareness through the prism of ecotourism. The innovativeness of the results obtained is revealed through the presented IDEF0 model.